The defence of African humanistic communalism for African pedagogy (2023)
Against the background of merely condemning Western paradigms for the African educational system, this paper integrates humanism and communalism as two concepts that can be combined to serve as a new orientation for an African pedagogy. African humanistic communalism would not be a celebration of a shattered past in the quest for an African meaning. Rather, it would be an attempt at going back to the root of all human efforts evidenced in the practice of togetherness and oneness where ‘we ness’ is greater than an exaggerated ‘I’. Past Pan-African authors like Nkrumah (1970) and Nyerere (1974) had earlier expressed African unity in their respective consciencism and self-reliance doctrines but they did not anchor their ideas on an appropriate pedagogy that could sustain the ideas more tangibly in educational systems. This paper used a systematic and critical analysis to call for a change in thinking that can strengthen the African educational systems through deliberate expressions of care for one another representative of a belief system.